Marknadsundersökning av färdigkapade produkter - Nilsson, Jonas (SLU/Dept. of Forest Products, 2010)
An increased demand for processed goods on the property market has contributed to investments within the Swedish sawmill industry. The purpose with this study is to make a market investigation of pre cut lengths within a defined geographic area. The constituent for this investigation is HAL (AB Hilmer Andersson) who invests in a new plane facility and two finger jointing machines in affiliation to their sawmill in Lässerud, the vest part of Värmland.